Penggunaan Aplikasi Laundry Sebagai Solusi Pengelolaan Keuangan dan Efisiensi Operasional pada SS Laundry Pontianak - Novita, Novita (Jurnal Akutansi Manajemen Ekonomi Kewirausahaan (JAMEK), 2025)
The use of laundry applications has now become a necessity for laundry businesses to manage transactions and finances more effectively and efficiently. This is also what SS Laundry, a laundry service business located in Pontianak, has done. This study aims to explore how the use of the Smartlink laundry application can improve operational efficiency and financial management in laundry businesses. Using a descriptive qualitative approach with a case study method, data in this study were collected through observation, interviews, documentation, and literature studies, and analyzed thematically to describe the experience of using the application in depth. The results show that the implementation of the Smartlink application has had a significant impact on the effectiveness of transaction recording, financial management, and operational efficiency of SS Laundry. Test results show that implementing the Smartlink application significantly improves system efficiency compared to manual methods. Transaction recording time is reduced by approximately 70%, error rates are reduced by 10%, and financial management is 85% faster due to real-time presentation. Furthermore, customer satisfaction has increased by 30% through the self-tracking feature for laundry processes. Administratively, staff requirements for recording are reduced by 100%, while operational costs remain relatively stable, offset by the additional benefits of data transparency, digital payments, and easy monitoring